The grammar of a problem like this can be more complicated than the algebra -- especially since English doesn't have as precise an order of operations as algebra. So it can be helpful to take it in small steps, and write down as much as possible so you can see what you're doing.

You made a great start, defining a variable and some expressions:

Aaron's age now = x

Casey's age now = x+4

Aaron's age in 3 years = x+3

Casey's age in 3 years = (x+4)+3 = x+7

Note that there is no reason not to simplify that last bit now, so there's less to copy wrong later.

Now put those into the problem:

Three times **Casey’s age in 3 years** = 2 less than 5 times **Aaron’s age in 3 years**.

Three times **(x + 3)** = 2 less than 5 times **(x + 7)**.

I used parentheses to make sure each expression is treated as a single quantity.

Now continue:

Three times (x + 3) = 3(x + 3)

2 less than 5 times (x + 7) = 5(x + 7) - 2

And the equation is

3(x + 3)= 5(x + 7) - 2

Are you okay with this last part?